2014
DOI: 10.1108/jsbed-05-2014-0090
|View full text |Cite
|
Sign up to set email alerts
|

The performance of entrepreneurial ventures

Abstract: Publisher's copyright statement:This article is c Emerald Group Publishing and permission has been granted for this version to appear here http://dro.dur.ac.uk/14711/. Emerald does not grant permission for this article to be further copied/distributed or hosted elsewhere without the express permission from Emerald Group Publishing Limited. Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…The more individual marketing managers use market information and apply it to solve managerial problems (instrumental use) as well as to broaden the managerial knowledge (conceptual use), the more small firm performance results are improved. Therefore, both instrumental and conceptual use of market information are complementary to firm performance, which is consistent with findings from previous research (Cillo et al, 2010;Parry and Song, 2010;Maltz et al, 2006) that also highlight the importance of management practices such as market research to enhance performance in entrepreneurial firms (Jayawarna et al, 2014).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The more individual marketing managers use market information and apply it to solve managerial problems (instrumental use) as well as to broaden the managerial knowledge (conceptual use), the more small firm performance results are improved. Therefore, both instrumental and conceptual use of market information are complementary to firm performance, which is consistent with findings from previous research (Cillo et al, 2010;Parry and Song, 2010;Maltz et al, 2006) that also highlight the importance of management practices such as market research to enhance performance in entrepreneurial firms (Jayawarna et al, 2014).…”
Section: Resultssupporting
confidence: 89%
“…, 2010; Parry and Song, 2010; Maltz et al. , 2006) that also highlight the importance of management practices such as market research to enhance performance in entrepreneurial firms (Jayawarna et al. , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The study argues that a business proposition should be not only desirable but also marketable. Webb et al (2011), Jayawarna et al (2014) and Lam and Harker (2014) emphasized the role of marketing in positively impacting start-up performance. They reported on the dearth of research linking effective marketing practices to potential and new venture performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Most entrepreneurs do not understand marketing, and often underestimate the time and effort needed to complete marketing activities (Hisrich, 1992;Özmaden et al, 2018). Entrepreneurs tend put low priority on marketing as they feel it is more suitable for larger organisations (Jayawarna et al, 2014). They might not use the word 'marketing' often, but marketing activities have played a crucial role in every stage of their business lifecycle (Lam and Harker, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These limitations include poor cash flow, lack of marketing expertise, business size, tactical and strategic customer-related problems (O'Dwyer et al, 2009) having few major clients (Jones and Rowley, 2011;Kolabi et al, 2011) shortness of staff, lack of management knowledge (Fillis, 2002;Jutla et al, 2002). Due to these limited resources, entrepreneurs focus more on short-term survival rather than long-term growth (Jayawarna et al, 2014;Peters and Zelewski, 2018). An earlier study conducted by Reijonen (2010) also found that marketing in SMEs focuses on present needs.…”
Section: Introductionmentioning
confidence: 99%